مساهمة مجالس سبل الخيرات في العمل الخيري( دراسة ميدانية ) - فهيمة بن عثمان (University of Eloued جامعة الوادي, 2024)
ملخص: مجلس سبل الخيرات أحد مجالس مؤسسة المسجد، و هو يمثل العمل التطوعي المؤسسي الذي يهدف إلى التكافل و التضامن بين أفراد المجتمع ، حيث يسطّر برنامجا سنويا في كل مديرية شؤون دينية في الجزائر ، حسب إمكانياتها المادية و تبرعات محسنيها و مواردها المالية ، ينضبط هذا المجلس بالتزام قوانين تنظم عمله و نشاطاته . تهدف هذه الدراسة الميدانية إلى معرفة نشاطات هذه المجالس الهامة في كل ولاية من ولايات الوطن إذ أن الاستبيان ووزع على كل ولايات الجزائر ، و تبحث في آفاق تطوير نشاطات هذه المجالس بحكم أن المجتمع في حاجة إلى ما تقدمه من مساعدات و أنشطة تكافلية.و قد توصلت الدراسة الميدانية إلى نتائج أهمها: تؤكد الدراسة على ضرورة خلق أملاك وقفية استثمارية لمجلس سبل الخيرات ، و تؤكد كذلك على ضرورة تشجيع المحسنين لوهب أملاك وقفية للمجلس، ذلك أن اعتماد المجلس على تبرعات المحسنين المحدودة يحد من فاعليته، و كذا ضرورة مساعدة المحتاجين ليتحولوا إلى منتجين فلا نكتفي بتقديم المساعدات الاستهلاكية التي تبقيهم محتاجين، و تدعوا الدراسة إلى إتاحة فرصة التطوع لكل فئات المجتمع كل حسب تخصصه. Abstract : The Council of Subul al-Khairat is one of the councils of the Mosque . It represents volunteering work that aims at solidarity and team work among members of society, as it draws up an annual program in each religious affairs directorate in Algeria, according to its financial capabilities, the donations of its benefactors, and its financial resources. This council is governed by commitment. Laws regulating his work and activities. This field study aims to know the activities of these important councils in each state of the country, as the questionnaire was distributed to all the states of Algeria, and examines the prospects for developing the activities of these councils, given that society is in need of the assistance and symbiotic activities they provide. The study emphasizes the necessity of creating property for the Subul al-Khair Council, and the necessity of encouraging volunteers to donate property to the Council, as the Council’s reliance on donations from benefactors limits its effectiveness, as well as the necessity of helping the needy to turn into producers, and the study calls for providing the opportunity to volunteer for all segments of society, each according to His specialty.
Keywords: سبل الخيرات; التكافل الاجتماعي; التعا; التضامن; مؤسسة المسجد; ways of good deeds; social solidarity; solidarity; mosque foundation